Creating value through mutual commitment to business network relationships - Holm, Desirée Blankenburg; Eriksson, Kent; Johanson, Jan (Strategic Management Journal, 1999)
A structural model of business relationship development in a business network context is formulated and tested on data from the European International Marketing and Purchasing (IMP) project. The empirical analysis demonstrates a causal chain from business network connection through mutual commitment and mutual dependence to value creation in the relationship. The results show that mutuality in business network relationships is critical in developing interfirm systems of workflow interdependence that promote the creation of value. This also implies that, through their interaction in business network relationships, firms in business markets organize and share an unbounded structure of interdependent activities, enabling them to achieve greater value than would be the case if they did not engage in relationship development. Copyright © 1999 John Wiley & Sons, Ltd.